Midwives’ Roles in Stunting Prevention Through Support During the First 1,000 Days: A Phenomenological Study - Dewi Umbarsari; Sri Wahyuni (Jurnal Ilmu Kesehatan Nusantara, 2025)
Background: Stunting remains a major public health challenge in Indonesia, requiring continuous prevention throughout the first 1,000 days of life. Midwives occupy a strategic position in providing maternal and child healthcare, yet their lived experiences in delivering community-based stunting prevention remain insufficiently explored locally. Research Objective: This study explored midwives’ roles, experiences, strategies, and challenges in preventing stunting through maternal support during the first 1,000 days. Methods: A descriptive phenomenological study was conducted in Jeneponto Regency, South Sulawesi, Indonesia, from November to December 2024. Fifteen midwives were recruited using purposive sampling. Data were collected through semi-structured in-depth interviews and analysed using Colaizzi’s seven-step method. Trustworthiness was ensured through member checking, peer debriefing, reflexivity, and an audit trail. Results: Five themes emerged: continuity of midwifery care; midwives as educators and behavioural-change agents; family and sociocultural influences; community-based collaboration; and structural barriers and adaptive strategies. Midwives provided clinical care, nutritional counselling, family engagement, cultural negotiation, growth monitoring, and interprofessional coordination. However, poverty, geographical barriers, workload, limited resources, and inconsistent family participation constrained continuous support. Conclusion: Midwives are central to integrated stunting prevention across the first 1,000 days. Strengthening staffing, transportation, professional development, family involvement, and multisectoral collaboration is necessary to deliver continuous, culturally responsive, and equitable maternal–child care.